Sonic environmental aesthetics and landscape research. (2nd January 2017) - Prior, Jonathan
Abstract: The environmental aesthetics literature has primarily focused on the aesthetic qualities and values of landscapes. Within this scholarship, there has been a modest but steady advancement towards explicitly attending to the aesthetic experience of landscape sounds. In this paper, I review the theoretical and applied sonic aesthetics literature pertinent to landscape research, and identify some existing weaknesses. In particular, I demonstrate that there is an ongoing tendency to limit discussions to what is sonically pleasing or displeasing within a given landscape, which, I argue, provides a limited point of entry through which to consider the full scope of landscape sounds. I then turn to offer some ways to address these weaknesses—notably through what I term the development of a 'sensitive ear', and through field recording strategies—in the hope that this will allow scholars to better enfold sonic environmental aesthetics within future theoretical and applied landscape research.